The Role of Artificial Intelligence Applications in Enhancing Educational Strategies in Higher Education (Literature Review) - Almalki, Wafa Fawaz (Journal of Educational and Psychological Sciences, 2023)
This study aimed to clarify the role of artificial intelligence applications in enhancing educational strategies in higher education. It also addressed the strategic benefits that educational institutions can obtain from integrating artificial intelligence in them, such as improving administrative functions, educational capabilities, research capabilities and improved learning environments, as well as potential obstacles. In front of its implementation, which may limit its effectiveness, such as resistance to change and technical restrictions, the study relied on the methodology of reviewing the narrative literature on twenty studies. There is an urgent need to educate stakeholders in education about the importance of using artificial intelligence applications in education strategies, and not to make challenges an obstacle to employing it in them.
Keywords: Artificial intelligence; applications of artificial intelligence; educational strategies